Conversion between the numerical simulation and the calculation using the Deformation Energy Ratio approach - Kirill Golubiatnikov; František Wald (MethodsX, 2025)
In numerical simulations and calculations, material curves are defined in different ways. A direct transfer of quantities between them is inaccurate, requiring a proper transformation of key values. The Deformation Energy Ratio approach is based on well-established mechanical principles, such as Neuber's rule and the Equivalent Strain Energy Density method, which express deformation energy as a function of stress and strain. This approach accounts for material conditions in both analyses and enables a more precise limit adjustment. Its simplicity allows for application in both analytical and numerical solutions. • Allows conversion of values between numerical simulation and calculation for any steel. • It takes into account the influence of material properties, thus comprehensively considering the effects of different factors. • The verification has presented a high accuracy of the values obtained. The average deviation is <5.0 % and the maximum deviation is 5.6 %.